What are the socio-political ethical models taught in the Patristic Church, especially in the Fathers, and in Plato’s Republic, and to what extent are these compatible? - Macadam, CJM (Cameron) (2024)
In this essay I will examine the social-political ethics which the Patristic Church taught as ideal and establish a spirutu partrum of the early Fathers of the Church, defined as those approximate to the death of Augustine. I will compare the social and political thought of the Fathers with those of Plato, as outlined in his Republic. I will begin by looking at the Patristic church and the writings of the Fathers, examining the taught models and practice of the faithful. In the first chapter I will consider what the underlying principles are and where the Fathers lack consensus, to establish a spectrum of Patristic socio-political thought. This will form the basis of a Patristic model. In the second chapter I will look at the kind of society Plato describes, this chapter will be devoted to examining principles, and preparing for the third chapter in which the Patristic and Platonic model of society can be compared, focusing on the comparable sacrificial attitude of Christian charity and the Platonic quest for justice. We begin by exploring Patristic consensus, and because the essay looks at a broad period and range of figures, it has required careful selection of the best and most appropriate sources and examples, but with such a vast period and range of figures cannot examine them all. Although primary sources will form a key part of this dissertation, they are not used exclusively, and compliment texts which give a broader, less proscriptive depiction of the Patristic church. The essay will examine not only the philosophical and theological, but the practical and lived expressions of these teachings. We will then make a judgement as to how compatible the Patristic and Platonic/Socratic models are, and whether the principles, as well as the practise of these ideas, are compatible.